A Study of Current situation, Difficulties, and Advantages of implementing BIM in the Construction Sector in Northern Iraq - Nazik Imad Saber; Khalil Ismail Wali (Zanco Journal of Pure and Applied Sciences, 2020)
Building Information Modeling (BIM) as an effective Technique of construction projects management has been adopted by the AEC (Architectural, Engineering, and Construction) industry. BIM has substantial benefits over the whole construction lifecycle. In spite of the importance of applying BIM in construction projects, It looks there is fewer study presented to rank the difficulties factors of implementing BIM , also there is less study conducted to show the advantages of using BIM in the construction sector in Northern Iraq. The major objective of this study is to investigate the current situation of applying BIM in the construction sector in Northern Iraq, examine the difficulties of implementing BIM and identify the advantages of implement BIM in the construction industry. A questionnaire was prepared and distributed to 276 engineers in three Governorates (Erbil, Kirkuk, and Sulaymaniyah) in both sectors (private and public). The collected data analyzed using the relative importance index (RII) and mean to rank the difficulties and advantages of implement BIM in Northern Iraq. The analysis results revealed that the most significant difficulties factors in adopting BIM in Northern Iraq are lack of education and syllabus in college regarding the sophisticated package, e.g., ArchiCAD and Revit, there is no training and tutoring for BIM applications in government departments and lack of government supporting and encouraging implementing BIM. The results also revealed the most significant advantages of using BIM are reduce risks in the design stage, improve building design and models, and improve the quality of the building.